Analisis Stabilitas Dinar emas dan Dolar AS dalam Denominasi Rupiah - Darwis Harahap (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2014)
Stability Analysis of Gold Dinar and US Dollar in Rupiah Denomination. This study was aimed to (a) to know if there is a causality relation between Gold Dinar and U.S. Dolar, (b) to know that Gold Dinar more stabil than U.S. Dolar AS, (c) to know whether Gold Dinar can be alternative currency as a substitute for U.S. Dolar. The result is that the growth of Gold Dinar higher than U.S. Dolar, the result of Granger causality test shown that there was undirectional causality from Gold Dinar to U.S. Dolar. The result of Analysis of Variance (ANOVA) shown that U.S. than Dinar Gold more stabil Dolar AS that measured by Rupiah. From all of result tests, it can conclude that Gold Dinar can be a alternative currency instead of U.S. Dolar.  DOI:10.15408/aiq.v6i2.1235